RANCANG BANGUN MESIN PEMBUATAN SARI TAPIOKA PADA PEMROSES GULA CAIR (SIRUP GLUKOSA) DARI SINGKONG (MANIHOT UTILLISSIMA) UNTUK INDUSTRI KECIL MENENGAH - Ig. Jaka Mulyana; L.M. Santosa Hadi Santosa; Yuliati Yuliati (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Sugar is one of the main sources of sweeteners and is widely used in the community. As one of the main ingredients in Indonesia, sugar demand in Indonesia has always increased along with the increase of population and industry growth in Indonesia. Meanwhile, sugar production in Indonesia can not meet domestic demand. Technically, the process of making glucose syrup is relatively simple and can be done by small or medium industries. But in fact glucose syrup producers are almost big industries. This is due to the development of a simple and cheap machine for making liquid sugar. Therefore, it is necessary to develop equipment to produce liquid sugar made from raw cassava, which can be used by small industry to develop liquid sugar industry. The process of making liquid sugar from cassava is divided into three namely the process of making tapioca, liquification and saccharification process and the process of tanning & filtering and evaporation. In this paper we will discuss the design of tapioca processing equipment which is part of the liquid cassava production equipment made from raw cassava that can be developed by small industry. With this equioment, the community can design a small industry of liquid sugar processing. This equipment aims to process cassava into cassava slurry. It is developed by using the principle of grinding and solvent. The processing capacity is designed to be 300 kg / hour.